SEARCH FOR TARGET TISSUE IN THE EYE ORBIT FOR AUTOIMMUNE AGGRESSION OF THYROID ANTIBODIES IN ENDOCRINE OPHTHALMOPATHY - V. G. Likhvantseva; M. S. Afanasiev; E. A. Rudenko; A. V. Karaulov; E. V. Korostelyova (Медицинская иммунология)
We searched for a possible target tissue in eye orbit for thyroid autoantibodies in endocrine ophthalmopathy (Graves’ disease), using correlation analysis method. We examined a group of 139 patients (278 eye orbits) with thyroid-associated ophthalmopathy associated with diffuse toxic goiter. Serological parameters (antibodies to thyroid-stimulating hormone receptor; thyroglobulin, thyroid peroxidase) were compared with instrumental diagnostic data (multi-layer CT, ultrasonography of eye orbit, and exophthalmometer), as well as clinical symptoms. Statistical correlation analysis enabled us to show different degrees of association between thyroid antibodies and clinical manifestations of Graves’ disease and eye orbit involvement. Especially, carriers of antibodies to TSH receptor and thyroglobulin (as compared to seronegative patients) exhibited higher exophthalmos scores (19.16±0.26 mm, p < 0.001, and 19.41±0.40 mm, p < 0.05, respectively), and with total muscle index (2.42±0.05, p < 0.01, and 2.42±0.08, respectively). Meanwhile, eyelids in carriers of antibodies to TSH receptor and thyroid peroxidase proved to be more swollen (p < 0.001, p < 0.05, respectively). Carriage of antibodies to thyroglobulin was associated with synchronous involvement of two structures of the eye orbit: extraocular muscles and retrobulbar tissue, which is reflected by increase in the average ntegral exophthalmos index within the group.